2023
DOI: 10.3389/fpsyg.2023.1116617
|View full text |Cite
|
Sign up to set email alerts
|

Cultivating organizational performance through the performance measurement systems: Role of psychological empowerment and creativity

Abstract: Interactive performance measurement systems (PMSs) play a critical role in shaping individual behavior and performance. To identify the underlying mechanism of how PMSs enhance organizational performance, a proposed model was constructed to investigate psychological empowerment and employee creativity as possible mediating variables. Based on a sample of 211 managers from Chinese organizations, a partial least squares structural equation modelling (PLS-SEM) approach was used to examine the mediating effect pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 77 publications
(193 reference statements)
0
0
0
Order By: Relevance
“…Specifically, this research concluded that OGC has a significant and positive effect on BuSuc (H3), which was in line with the previous papers [30,32] which determined a highly positive influence of OGC on BuSuc based on the RBV theory perspective. Hence, it fulfilled the deficiency of empirical examinations on the relationships between OGC and BuSuc [99]. Besides that, unlike Setyaningrum et al [26] who found a negative influence of green OGC on BuSuc, our results strongly favored the extant investigations [100][101][102][103] which proposed the significant and valuable implications of OGC for organizational outcomes.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Specifically, this research concluded that OGC has a significant and positive effect on BuSuc (H3), which was in line with the previous papers [30,32] which determined a highly positive influence of OGC on BuSuc based on the RBV theory perspective. Hence, it fulfilled the deficiency of empirical examinations on the relationships between OGC and BuSuc [99]. Besides that, unlike Setyaningrum et al [26] who found a negative influence of green OGC on BuSuc, our results strongly favored the extant investigations [100][101][102][103] which proposed the significant and valuable implications of OGC for organizational outcomes.…”
Section: Discussionsupporting
confidence: 75%
“…However, empirical investigations on the association between OGC and BuSuc are scarce [99]. Moreover, Setyaningrum et al [26] found a significant negative effect of green OGC on green SMEs' outcomes.…”
Section: H1 Entrepreneurial Financial Support (H1a) and Entrepreneuri...mentioning
confidence: 99%